Design of a Grid-connected Photovoltaic Inverter with Maximum Power Point Tracking using Perturb and Observe Technique - M. Abdur Razzak; Wahida Taskin Bhuiyan; Nawrin Islam Natasha; A K M Muzahidul Islam; Muhamad Kamal Mohammed Amin (Institute of Advanced Engineering and Science, 2016)
There is no easy way to convert Photovoltaic (PV) energy with high efficiency due to dynamic changes in solar irradiance and temperature. This paper illustrates a control strategy to design and implementation of Maximum Power Point Tracking (MPPT) in a photovoltaic system using Perturb and Observe (P&O) algorithm. The PSIM simulation results confirm proper functioning of the proposed MPPT sub-circuit to achieve a constant 48V DC output from fluctuating voltage of solar panel by varying duty cycle of the MOSFET in the 24V-48V boost converter. The filtered output waveform of the SPWM driven H-bridge inverter via the L-C low pass filter is found to be a pure sine-wave of 48V peak which is then stepped-up 312V peak (220V rms) by using a step up transformer. The frequency of output voltage is found to be 50Hz with a total harmonic distortion (THD) of 0.001 which is much lower than the IEEE 519 standard.